Assessment of bacterial communities of Coptotermes gestroi termite workers attacking Ironwood trees (Casuarina equisetifolia) in Guam for the presence of Ironwood tree decline-associated pathogens - Setia, Garima; Chen, Junyan; Schlub, Robert; Husseneder, Claudia (Frontiers in Microbiology, 2024)
The Ironwood tree (Casuarina equisetifolia) holds a significant ecological role in Guam where a decline in Ironwood trees was first documented in 2002. Studies have linked the Ironwood tree decline (IWTD) to bacteria from the Ralstonia solanacearum complex and wetwood bacteria, specifically Klebsiella oxytoca and Klebsiella variicola. Presence of termites was first found to be associated with IWTD in 2010; however, the role of termites in IWTD is still not clear. The Asian subterranean termite, Coptotermes gestroi (Wasmann) (Blattodea: Rhinotermitidae) frequently attacks Ironwood trees. As workers of this soil-dwelling species of the lower termites harbor a diverse microbial community in their bodies, we examined whether C. gestroi workers carry IWTD-associated bacteria and could, therefore, act as vectors. We described the bacterial community in C. gestroi workers using 16S rRNA gene sequencing and tested the impact of factors related to the location and health of the Ironwood tree the termites were collected from on termite bacterial diversity. Feeding assays were performed to assess if workers show preference in consumption depending on the amount of Ralstonia and wetwood bacteria in the food source. Health of Ironwood trees and level of site management impacted the bacterial composition of C. gestroi termite workers attacking the trees. Although C. gestroi workers equally consumed food sources with high and low Ralstonia and wetwood bacteria load in lab experiments, Ralstonia and other IWTD-related bacteria were not detected in considerable amounts in termite workers collected from trees. Thus, C. gestroi workers are not a vector for bacteria associated with IWTD in Guam.